Users Perception of the Mobile Usability of a Global Bicycle Sharing Platform - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Nabeel, Noor; Alathwari, Ahmed (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Global bicycle sharing platform offers commuters an accessible, convenient and eco-friendly alternative mode of transport. The study reports on the users’ perception about the mobile usability of oBike, a global bicycle sharing platform. Fifteen participants were recruited for the study. The study outcome reveals that most of the participants found that the oBike mobile application needs to be enhanced to improve their satisfaction. Some recommendations were proffered that if implemented will guarantee the improvement of the application.